Upconverting nanoparticles as nano-transducers for photodynamic therapy in cancer cells - Chatterjee, D.K. (2014)
Technical Proceedings of the 2008 NSTI Nanotechnology Conference and Trade Show, NSTI-Nanotech, Nanotechnology 2008